Management and outcome of major bleeding in patients receiving vitamin K antagonists for venous thromboembolism. Issue 171 (November 2018) - Moustafa, Farès; Stehouwer, Alexander; Kamphuisen, Pieter; Sahuquillo, Joan Carles; Sampériz, Ángel; Alfonso, María; Pace, Federica; Suriñach, José María; Blanco-Molina, Ángeles; Mismetti, Patrick; Monreal, Manuel; ,
Abstract: Background: The optimal management of major bleeding in patients receiving vitamin K antagonists (VKA) for venous thromboembolism (VTE) is unclear. Methods: We used the RIETE (Registro Informatizado Enfermedad TromboEmbólica) registry to assess the management and 30-day outcomes after major bleeding in patients receiving VKA for VTE. Results: From January 2013 to December 2017, 267 of 18, 416 patients (1.4%) receiving long-term VKA for VTE had a major bleeding (in the gastrointestinal tract 78, intracranial 72, hematoma 50, genitourinary 20, other 47). Overall, 151 patients (57%) received blood transfusion; 110 (41%) vitamin K; 37 (14%) fresh frozen plasma; 29 (11%) pro-haemostatic agents and 20 (7.5%) a vena cava filter. During the first 30 days, 59 patients (22%) died (41 died of bleeding) and 13 (4.9%) had a thrombosis. On multivariable analysis, patients with intracranial bleeding (hazard ratio [HR]: 4.58; 95%CI: 2.40–8.72) and those with renal insufficiency at baseline (HR: 2.73; 95%CI: 1.45–5.15) had an increased mortality risk, whereas those receiving vitamin K had a lower risk (HR: 0.47; 0.24–0.92). On the other hand, patients receiving fresh frozen plasma were at increased risk for thrombotic events (HR: 4.22; 95%CI: 1.25–14.3). Conclusions: Major bleeding in VTE patients receiving VKA carries a high mortality rate. Intracranial bleeding and renal insufficiency increased the risk. Fresh frozen plasma seems to increase this risk for recurrent VTE. Highlights: Optimal management of major bleeding in patients receiving VKA for venous thromboembolism is still unclear. Major bleeding occurred in 1.4% of patients with mortality ranged from 6.0% (haematoma) to 42% (intracranial bleeding). Only 41% of patients received vitamin K, 11% received prohemostatic agents and 7.5% underwent a vena cava filter. Patients receiving vitamin K were at lower risk to die, and those receiving FFP at increased risk for thrombotic events.